Les portraits de Marie-Thérèse Représentation et lien politique dans la Monarchie des Habsbourg (1740-1780) - Banakas, Anne-Sophie (De Gruyter, 2021)
In the Austrian monarchy, Maria Theresa is the first and only woman of the Habsburg dynasty to rule and impose herself in a context of wars and reforms. In a situation of multiform crises (territorial dynasty, etc.), the representation and dissemination of the image of the sovereign through portraits is an essential aspect of royal politics. These portraits and their analysis are at the heart of this book.